SHLD2/FAM35A co‐operates with REV7 to coordinate DNA double‐strand break repair pathway choice. (28th August 2018) - Findlay, Steven; Heath, John; Luo, Vincent M; Malina, Abba; Morin, Théo; Coulombe, Yan; Djerir, Billel; Li, Zhigang; Samiei, Arash; Simo‐Cheyou, Estelle; Karam, Martin; Bagci, Halil; et al.
Abstract: DNA double‐strand breaks (DSBs) can be repaired by two major pathways: non‐homologous end‐joining (NHEJ) and homologous recombination (HR). DNA repair pathway choice is governed by the opposing activities of 53BP1, in complex with its effectors RIF1 and REV7, and BRCA1. However, it remains unknown how the 53BP1/RIF1/REV7 complex stimulates NHEJ and restricts HR to the S/G2 phases of the cell cycle. Using a mass spectrometry (MS)‐based approach, we identify 11 high‐confidence REV7 interactors and elucidate the role of SHLD2 (previously annotated as FAM35A and RINN2) as an effector of REV7 in the NHEJ pathway. FAM35A depletion impairs NHEJ‐mediated DNA repair and compromises antibody diversification by class switch recombination (CSR) in B cells. FAM35A accumulates at DSBs in a 53BP1‐, RIF1‐, and REV7‐dependent manner and antagonizes HR by limiting DNA end resection. In fact, FAM35A is part of a larger complex composed of REV7 and SHLD1 (previously annotated as C20orf196 and RINN3), which promotes NHEJ and limits HR. Together, these results establish SHLD2 as a novel effector of REV7 in controlling the decision‐making process during DSB repair. Synopsis: Proteomic interaction and CRISPR/Cas9 doxorubicin sensitivity screens identify shieldin proteins as the sought‐after effectors through which the 53BP1/RIF1/REV7 axis antagonizes homologous recombination (HR) and promotes non‐homologous end‐joining (NHEJ) repair of DNA double strand breaks (DSB). Mass spectrometry identifies SHLD2/FAM35A as REV7 interactor. SHLD2 is recruited to DSBs and promotes their repair. SHLD2 promotes NHEJ and antagonizes HR by inhibiting DNA end resection. SHLD2 is part of a larger multi‐protein complex composed of REV7 and SHLD1/C20orf196. SHLD2 is a biomarker for the prognosis of TNBC/basal‐like BC. Abstract : Proteomic interaction and CRISPR/Cas9 doxorubicin sensitivity screens identify the sought‐after effectors through which the 53BP1/RIF1/REV7 axis antagonizes DNA break resection and promotes non‐homologous end‐joining repair.